440. The Masqueraders Presenting a Multisystem Disease: Unusual and Atypical Clinical Features of Scrub Typhus in Fukushima, Japan. (26th November 2018) - Narita, Masashi; Nakamura, Kiwamu; Monma, Naota; Chiba, Kazuki; Suzuki, Rie; Inoue, Minoru; Fujita, Hiromi
Abstract: Background: Scrub typhus (ST) is endemic in Fukushima, where the highest number has been reported from 2006 to 2011 in Japan. Atypical clinical presentation of ST makes the diagnosis difficult followed by treatment delay. Despite fatal but treatable disease with early recognition, the myriad clinical features of ST have been underreported. Methods: We reviewed the clinical features of adult patients diagnosed as ST from 2008 to 2017 at Ohta Nishinouchi General Hospital, a major teaching hospital in Fukushima, Japan. Results: Total 55 cases (serotype Karp 24, Irie/Kawasaki 21, Hirano/Kuroki 10) of ST were confirmed by elevated specific IgM and IgG in the paired sera and real-time PCR analysis of eschars. Unusual presentations as the main clinical features of ST are found in 7/55 (13%; Karp 4 and Irie/Kawasaki 3), including cardiovascular (3 cases of paroxysmal atrial fibrillation), neurological (2 cases of syncope and one case of encephalitis) and metabolic/electrolyte disorder (one case of hyponatremia). In terms of atypical clinical features, the cases without triad (fever ≥38.0℃, rash and eschar) were found in 14/55 (25%). The cases of "eschar negative scrub typhus" were found in 6/55 (11%; Karp 1, Irie/Kawasaki 2, Hirano/Kuroki 3). The cases without fever and rash were also found in 6/55 (11%; Karp 2, Irie/Kawasaki 3, Hirano/Kuroki 1) and 4/55 (7%; Karp 2, Irie/Kawasaki 1, Hirano/Kuroki 1), respectively. Severe cases (4/55, 7%) were found with shock and disseminated intravascular coagulation including one fatal case (1/55, 1.8%; Hirano/Kuroki). Besides more than the half of ST cases with triad (30/55; 55%), unusual and atypical presentations were found in 38% (21/55) of the total number of cases. Conclusion: The diagnosis of ST is a clinical challenge without typical features. In endemic area, unusual and atypical presentation of ST involving multi-system should be noted as the odds-on favorite differential diagnosis. Disclosures: All authors: No reported disclosures.